Optimizing Laser-Induced Voltage Signal in SnO2 Thin Films by Changing Oxygen Pressure - Xiaohong Zhou; Xiaofang Zhou; Hui Zhang (Advances in Materials Science and Engineering)
Laser-induced voltage (LIV) effect of the thin film can be applied for the laser energy measurement and millimeter-wave detection. The amplitude and corresponding velocity of LIV signals depended on the film material and preparation process. In the study, the effect of oxygen pressure on the LIV signals of SnO2 thin films was studied and got the surprised result that the maximum LIV peak reach about 4.02 V and response time with only 98 ns when oxygen pressure was 30 Pa. The crystal quality of the films was analyzed by X-ray diffraction (XRD) and LIV measurements, and a linear relationship between LIV peak voltage and laser energy was also disclosed. Those findings indicate that the laser energy/power meters designed with SnO2 thin film with optimized oxygen pressure would have the merits high precision, high sensitivity, and fast response.